2010
DOI: 10.1128/aac.01570-09
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Selectivity of Antibiotic Kinases

Abstract: Antibiotic kinases, which include aminoglycoside and macrolide phosphotransferases (APHs and MPHs), pose a serious threat to currently used antimicrobial therapies. These enzymes show structural and functional homology with Ser/Thr/Tyr kinases, which is suggestive of a common ancestor. Surprisingly, recent in vitro studies using purified antibiotic kinase enzymes have revealed that a number are able to utilize GTP as the antibiotic phospho donor, either preferentially or exclusively compared to ATP, the canoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Macrolide 2 0 -phosphotransferases, commonly found on mobile genetic elements, are inducible (e.g., mph(A)) or constitutively expressed (e.g., mph(B)) intracellular enzymes capable of transferring the g-phosphate of nucleotide triphosphate to the 2 0 -OH group of 14-, 15-, and 16-membered-ring macrolide antibiotics, thereby disrupting the macrolide's key interaction with A2058. Although early studies showed Mph enzymes could use ATP, more recent work with Mph(A) has shown a preference for GTP under physiologically relevant in vitro assay conditions (Shakya and Wright 2010). Expression of mph(A) is induced by erythromycin, and, recently, the structure of the MphR(A) repressor protein, a negative regulator of mph(A) expression, has been solved uncomplexed and complexed with erythromycin to 2.00 Å and 1.76 Å resolutions, respectively (Zheng et al 2009).…”
Section: Phosphotransferasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrolide 2 0 -phosphotransferases, commonly found on mobile genetic elements, are inducible (e.g., mph(A)) or constitutively expressed (e.g., mph(B)) intracellular enzymes capable of transferring the g-phosphate of nucleotide triphosphate to the 2 0 -OH group of 14-, 15-, and 16-membered-ring macrolide antibiotics, thereby disrupting the macrolide's key interaction with A2058. Although early studies showed Mph enzymes could use ATP, more recent work with Mph(A) has shown a preference for GTP under physiologically relevant in vitro assay conditions (Shakya and Wright 2010). Expression of mph(A) is induced by erythromycin, and, recently, the structure of the MphR(A) repressor protein, a negative regulator of mph(A) expression, has been solved uncomplexed and complexed with erythromycin to 2.00 Å and 1.76 Å resolutions, respectively (Zheng et al 2009).…”
Section: Phosphotransferasesmentioning
confidence: 99%
“…Macrolide phosphotransferases are macrolideinactivating enzymes widespread in Gram-negative and Gram-positive bacteria (Sutcliffe and Leclercq 2002;Roberts 2008) that, by in silico analysis, are in the same family as aminoglycoside and protein kinases (Shakya and Wright 2010). The first reported purifications of macrolide-2 0 -phosphotransferases were from macrolide-resistant E. coli, and this mechanism was soon shown to be prevalent in E. coli clinical isolates in Japan (O'Hara et al 1989;Kono et al 1992;Taniguchi et al 2004).…”
Section: Phosphotransferasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work on the APHs from the aminoglycoside-2ЈЈ-phosphotransferase [APH(2ЈЈ)] subfamily (25) have shown that not only are these enzymes capable of using GTP as the phosphate source but that two members of this family (APH(2ЈЈ)-Ia and APH(2ЈЈ)-IIIa) utilize GTP exclusively in vivo. The ability of the APH(2ЈЈ) enzymes to use GTP as a cofactor is unexpected, as APHs were also considered to be exclusively ATP-dependent (20,26). This raises a number of questions related to nucleotide binding and catalysis in the aminoglycoside kinases and in the protein kinases in general.…”
mentioning
confidence: 99%
“…In contrast, APH(4)-Ia demonstrated the ability to utilize both ATP and GTP as a phosphate donor with ϳ5-fold preference toward ATP based upon the k cat /K m values of 5.42 ϫ 10 4 and 1.04 ϫ 10 4 , respectively. Similar nucleotide promiscuity has been previously observed for the APH(2Љ) class of enzymes (31,32). In eukaryotic protein kinases, the capacity to utilize GTP is rare, and this difference could be exploited in the development of specific inhibitors.…”
Section: Substrate and Regiospecificities Of Aph(4)-ia-previous En-mentioning
confidence: 56%